THE INTERPLAY OF CARBON DISCLOSURE, ENVIRONMENTAL PERFORMANCE, AND PROFITABILITY IN DETERMINAN FIRM VALUE - Kamaluddin, Nurhadi; Saputro, Ilham Fajar Eko; Ulfah, Nadiyah (Pendidikan Ekonomi FPEB Universitas Pendidikan Indonesia, 2024)
This study aims to determine the effect of carbon emission disclosure, environmental performance, and profitability on firm value. This study uses a quantitative approach using secondary data. The sampling method used is purposive sampling. The sample used is mining companies listed on the Indonesia Stock Exchange in 2020-2022 totaling 16 companies. The hypothesis was tested using IBM SPSS 25 with Multiple Linear Regression Analysis techniques. The results showed that Carbon Emission Disclosure and Environmental Performance partially had a significant positive effect on Firm Value. While Profitability partially has a significant negative effect on Firm Value. Simultaneously, Carbon Emission Disclosure, Environmental Performance and Profitability have a significant positive effect on Firm Value. This study adds profitability variables as independent variables. The research was conducted on mining companies listed on the Indonesia Stock Exchange for 3 periods from 2020 to 2022.